Facile synthesis of N-substituted maleimides - Deshpande, Sunita R.; Maybhate, Shailaja P.; Likhite, Anjali P.; Chaudhary, Preeti M. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2010)
A simple and efficient method for the synthesis of N-substituted malemides from the corresponding maleamie acids under the phase transfer catalysis has been described
Keywords: Maleamic acids; maleimides; phase transfer catalysis; synthesis